First-line treatment of anti-EGFR monoclonal antibody cetuximab β plus FOLFIRI versus FOLFIRI alone in Chinese patients with RAS/BRAF wild-type metastatic colorectal cancer: a randomized, phase 3 trial - Yuankai Shi; Yi Ba; Junye Wang; Jianping Xiong; Kangsheng Gu; Yigui Chen; Zhendong Zheng; Zishu Wang; Weijian Guo; Ying Cheng; Xianli Yin; Yunpeng Liu; et al. (Signal Transduction and Targeted Therapy)
Abstract Cetuximab plus irinotecan, fluorouracil, and leucovorin (FOLFIRI) represents a first-line therapeutic standard for RAS/BRAF wild-type metastatic colorectal cancer (mCRC) patients. Despite this established approach, cetuximab β (CMAB009), as a modified antibody of cetuximab, prospectively selected for dual RAS/BRAF wild-type patients, has not yet been validated in the Chinese mCRC patients through phase 3 trial. In this study (ClinicalTrials.gov identifier: NCT03206151), patients with RAS/BRAF wild-type mCRC who were not suitable for radical resection were randomly assigned in a 1:1 ratio to receive cetuximab β plus FOLFIRI or FOLFIRI alone. The primary endpoint was blinded independent review committee-assessed progression-free survival (PFS). The secondary endpoints included overall survival (OS), objective response rate (ORR), disease control rate (DCR), surgery rate for metastasis and R0 resection rate, and safety. From January 4, 2018 to September 2, 2021, a total of 505 eligible patients were enrolled and received study treatment; the median follow-up duration was 8.7 months (95% confidence interval [CI], 7.77 to 9.29) and 5.9 months (95% CI, 5.63 to 6.65) in cetuximab β plus FOLFIRI group and FOLFIRI group, respectively. Compared to FOLFIRI alone, cetuximab β plus FOLFIRI demonstrated statistically significant improvements in median PFS (13.1 vs. 9.6 months, hazard ratio [HR], 0.639; 95% CI, 0.468 to 0.872; P = 0.004), median OS (28.3 vs. 23.1 months, HR, 0.729; 95% CI, 0.551 to 0.965; P = 0.024), and ORR (69.1% vs. 42.3%, odds ratio, 3.090; 95% CI, 2.280 to 4.189; P < 0.001). Cetuximab β plus FOLFIRI exhibited manageable toxicity without novel safety signals. This study demonstrated that cetuximab β plus FOLFIRI provided significant clinical benefits as a first-line treatment for patients with RAS/BRAF wild-type mCRC. Compared to FOLFIRI alone, cetuximab β plus FOLFIRI therapy led to prolonged median PFS and OS while maintaining a manageable safety profile, offering a new treatment option for this patient population.